2001
DOI: 10.1046/j.1439-0523.2001.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

A microsatellite marker linked to leaf rust resistance transferred from Aegilops triuncialis into hexaploid wheat

Abstract: Aegilops triuncialis (UUCC) is an excellent source of resistance to various wheat diseases, including leaf rust. Leaf rust‐resistant derivatives from a cross of a highly susceptible Triticum aestivum cv.‘WL711’ as the recurrent parent and Ae. triuncialis Ace.3549 as the donor and with and without a pair of acrocentric chromosomes were used for molecular tagging. The use of a set of sequence tagged microsatellite (STMS) markers already mapped to different wheat chromosomes unequivocally indicated that STMS mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…None of the tested 23 SSRs of chromosomes 5A and 4B identified the A. triuncialis ‐specific introgression in the translocation line TA5605 (data not shown). This suggested that either the leaf rust resistant introgression in TA5605 is different from previous reports of Aghaee‐Sarbarzeh et al (2001, 2002) or the marker density might not be enough to detect the leaf rust resistant introgression of A. triuncialis in TA5605. Bulked segregant analysis of the homozygous resistant and susceptible F 2 bulks was used for chromosome mapping and tagging of the leaf rust resistant introgression using distally mapped RFLP markers.…”
Section: Resultscontrasting
confidence: 59%
See 3 more Smart Citations
“…None of the tested 23 SSRs of chromosomes 5A and 4B identified the A. triuncialis ‐specific introgression in the translocation line TA5605 (data not shown). This suggested that either the leaf rust resistant introgression in TA5605 is different from previous reports of Aghaee‐Sarbarzeh et al (2001, 2002) or the marker density might not be enough to detect the leaf rust resistant introgression of A. triuncialis in TA5605. Bulked segregant analysis of the homozygous resistant and susceptible F 2 bulks was used for chromosome mapping and tagging of the leaf rust resistant introgression using distally mapped RFLP markers.…”
Section: Resultscontrasting
confidence: 59%
“…The introgression line was developed by crossing the susceptible hexaploid wheat cultivar WL711 with rust‐resistant A. triuncialis (TA10438, PAU no. 3549) and backcrossing the resultant F 1 with WL711 (Harjit‐Singh et al, 2000; Aghaee‐Sarbarzeh et al, 2001). Leaf rust resistant BC 1 F 1 plants were selected, backcrossed further to WL711 and selfed to develop BC 3 F 11 lines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…biuncialis, and Ae. speltoides have shown rust resistance (Aghaee-Sarbarzeh et al, 2001;Schneider et al, 2008); Ae. geniculata is resistant to powdery mildew (Stoilova and Spetsov, 2006) and BYDV (Barley Yellow Dwarf Virus) (Zaharieva et al, 2001b); Ae.…”
Section: Introductionmentioning
confidence: 99%